2020
DOI: 10.1002/adom.201901536
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Near‐Infrared Harvesting Transparent Luminescent Solar Concentrators

Abstract: the architectural envelope as they become more scalable, converting new and existing infrastructure into power-generating sources and dramatically reducing the electrical loss in transmission. [4,5] Transparent luminescent solar concentrators (TLSCs), a key TPV technology, optically shift the solar energy conversion by photoluminescence (PL) that is transported optically (by total internal reflection) to edge-mounted PV cells ( Figure 1A). [1] Due to the absence of electrodes, busbars, and collection grids ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…[266] The design of LSCs for solar window application cannot exclusively focus on performances but requires the definition of appropriate balance between efficiency, optical transparency, and social acceptability. [6,7,[270][271][272][273][274] This problem is far from trivial since until now, large-scale LSCs are poorly efficient and a constraint of transparency can impose a further limitation to the efficiency. Wiegman et al investigated the optical properties of an LSC based on 3 µm thin films of europium-doped Lu 2 O 3 in view of possible application in BIPV but the efficiency was strongly limited by scattering losses.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
See 1 more Smart Citation
“…[266] The design of LSCs for solar window application cannot exclusively focus on performances but requires the definition of appropriate balance between efficiency, optical transparency, and social acceptability. [6,7,[270][271][272][273][274] This problem is far from trivial since until now, large-scale LSCs are poorly efficient and a constraint of transparency can impose a further limitation to the efficiency. Wiegman et al investigated the optical properties of an LSC based on 3 µm thin films of europium-doped Lu 2 O 3 in view of possible application in BIPV but the efficiency was strongly limited by scattering losses.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The system shows a high optical transmittance of 75% and a PCE of 1.24% with J sc ≈ 2 mA cm -2 but C was largely inferior to unity. [274] Recent work has presented original approaches to light-managing systems combining the specific properties of LSCs with switchability that allows to envision some future advanced light-managing BIVP systems combining controlled transmittance and PV generation. [275][276][277] Although BIPV is certainly one of the most promising applications of LSCs, work devoted to the realization of systems with dimensions close to real utilization remains scarce, most of the recent work deals with devices of a few square centimeters while LSCs of 100 cm 2 are generally qualified as "large-area LSCs."…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…In the first camp, the performance of LSCs is mostly evaluated using the same metrics already widely adopted by the PV community, relying on the solar-to-electrical power conversion efficiency as the fundamental figure of merit. [16][17][18][19][20][21][22] This metric certainly becomes important when discussing the commercialisation and deployment of the LSC device into the built environment at the industrial level, as it provides a single, easy-to-understand number that may be used to advertise and sell devices, and gives system designers the means to make calculations as to the impact of the device in their architectures. However, it is much less useful in the research process at the laboratory scale.…”
mentioning
confidence: 99%
“…[ 13–16 ] The proposed wavelength‐selective TPV developed in this work exhibits a maximum AVT of approximately 77.45%, which is the highest value compared with the previous work in the TPVs, [ 1–3 ] not segmented PVs, [ 56 ] or transparent luminescent solar concentrators. [ 17,18 ] The TPV devices' surface morphology with different electrodes were analyzed by AFM measurements (see Figure S5, Supporting Information). It can be observed that the TPV device with Ag/WO 3 electrode is relatively rough (RMS = 2.63 nm) contributed from the obvious aggregation and granular structure.…”
Section: Resultsmentioning
confidence: 99%
“…Later on, the research team by Lunt also demonstrated another approach with the NIR harvesting transparent luminescent solar concentrators (LSCs). [ 17,18 ] The transparent LSCs exhibited nontinted transparency >86% in the visible‐light with edge‐mounted Si PV to achieve the PCE > 0.4%. Therefore, TPV with high transparency has great potential in unique solar energy applications, which improves the device performance.…”
Section: Introductionmentioning
confidence: 99%